2020
DOI: 10.1136/bmjopen-2020-040380
|View full text |Cite
|
Sign up to set email alerts
|

Temporal profile and determinants of viral shedding and of viral clearance confirmation on nasopharyngeal swabs from SARS-CoV-2-positive subjects: a population-based prospective cohort study in Reggio Emilia, Italy.

Abstract: Objectives To determine the timing of viral clearance (first negative RT-PCR on nasopharyngeal swab) and the probability of viral clearance confirmation (two consecutive negative swabs) in COVID-19 patients and to identify related determinants. Design Population-based prospective cohort study on archive data. Setting Preventive services and hospital care in the Reggio Emilia province, northern Italy. Participants All 1162 subjects testing positive to RT-PCR on nasopharyngeal swabs and diagnosed with COVID-19 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 23 publications
3
27
0
1
Order By: Relevance
“…Our results are in accordance with the work of Mancuso et al (16) which demonstrated in a sample of 1162 patients that 60,6% of subjects became negative at a median follow up time of 30 days from diagnosis and 36 days from symptoms onset. Moreover, in a recent submitted article, available in pre-print, Lombardi et al reported a median time from rst positive test to a negative test to be 27 days (95% CI: 24-30) (17).…”
Section: Discussionsupporting
confidence: 94%
“…Our results are in accordance with the work of Mancuso et al (16) which demonstrated in a sample of 1162 patients that 60,6% of subjects became negative at a median follow up time of 30 days from diagnosis and 36 days from symptoms onset. Moreover, in a recent submitted article, available in pre-print, Lombardi et al reported a median time from rst positive test to a negative test to be 27 days (95% CI: 24-30) (17).…”
Section: Discussionsupporting
confidence: 94%
“…Our results are in accordance with the work of Mancuso et al (17) which demonstrated in a sample of 1162 patients that 60,6% of subjects became negative at a median follow up time of 30 days from diagnosis and 36 days from symptoms onset. Moreover, in a recent submitted article, available in preprint, Lombardi et al reported a median time from rst positive test to a negative test to be 27 days (95% CI: 24-30) (18).…”
Section: Discussionsupporting
confidence: 94%
“…60.6% of the subjects achieved viral clearance with a median time of 36 days from the symptoms onset. There was an association between the age and the viral clearance which increased slightly in older patients (>80 years) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%